KINERJA KEUANGAN DAN PENGUNGKAPAN CORPORATE RESPONSIBILITY PERBANKAN SYARIAH DI INDONESIA - Miqdam Maufur; Abdul Basit; Akmal Ihsan; M. Zidny Nafi’ Hasbi (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
Performance has an effect on CSR disclosure of Islamic Commercial Banks in Indonesia. The financial performance variable uses the profitability ratios (ROA, ROE, NIM), while the CSR measurement uses the ISR indicator. The sample in this study uses 6 Islamic Commercial Banks with a data period from 2014-2016. Data analysis in this study used multiple linear regression. The results of this study are Return on Assets (ROA) has a significant positive effect on CSR disclosure, Return on Equity (ROE) has a significant positive effect on CSR disclosure, and Net Income Margin (NIM) has an insignificant positive effect on CSR disclosure. Together, the ROA, ROE, and NIM variables have a significant effect on the disclosure of Islamic Bank CSR in Indonesia in 2014-2019.